Protective effect of sucupira oil nanoemulsion against oxidative stress in UVA‐irradiated HaCaT cells. (4th August 2019) - Pacheco, Maiulle T.; Silva, Artur C. G.; Nascimento, Thais L.; Diniz, Danielle G. A.; Valadares, Marize C.; Lima, Eliana M.
Abstract: Objectives: Bioactive molecules derived from natural products combine the ability to absorb UV light and act as antioxidants. We developed an oil‐based sucupira (native species of the Brazilian cerrado) nanoemulsion (NE) using a high‐energy emulsification method and assessed its effectiveness in vitro . Methods: An easily scalable high‐pressure homogenization method was used to prepare the formulation. NE droplets mean diameter, pH, stability, conductivity and morphology were analysed. Formulation bioactivity was assessed using HaCaT cells. Key findings: The formulation presented suitable pH and size for topic administration and was stable for over 90 days upon storage at 4, 25 and 45°C. The NE showed protective effect against oxidative stress and reduced levels of UVA‐induced pro‐inflammatory cytokines IL‐6 and IL‐8. Conclusions: A novel, stable and easily prepared formulation was obtained for encapsulation of sucupira oil. The protective effect of the formulation by cytokine inhibition in the early stage of the inflammatory process was shown in vitro . Combined with the antioxidant effect by inhibition of reactive oxygen species, the use of sucupira oil NE for prevention and treatment of UVA‐induced stress could contribute to decrease the effects of UV radiation on skin ageing.